Effect of sintering temperature on phase formation, dielectric, piezoelectric, and ferroelectric properties of Nb-doped Pb(Zr 0.52ti0.48)O3 ceramics - Ketsuwan P. (2014)
The effects of sintering temperature on physical and electrical properties of the Pb(Zr0.52Ti0.48)O3 ceramics with addition of 1wt% Nb2O5 prepared by conventional mixed oxide technique were investigated. The samples were sintered over temperature rang 1200-1300°C. At lower sintering temperature, the dominant phase was rhombohedral while the tetragonal phase became dominant at higher temperature. The dielectric constant increased with increasing sintering temperature from 1200 to 1250°C. Further increase in temperature resulted in a drop of the dielectric constant. Similar trend was also observed for the d 33-constant. For the ferroelectric properties, the electrical coercivity and remnant polarization decreased with increasing sintering temperature.